1994
DOI: 10.1002/bmc.1130080611
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatographic analysis of polypeptide hormones in transplanted rat islets

Abstract: This report describes high performance liquid chromatographic analysis of transplanted pancreatic islets. A reversed phase ODS column made it possible to measure rat insulin I, II, rat C-peptide I, II and glucagon simultaneously in isolated rat islets without using radioisotopes. Freshly isolated islets contained 118.0 +/- 9.7 ng (mean +/- SE, n = 6) insulin and 3.01 +/- 0.60 ng glucagon per islet. The insulin I/II ratio was 1.22 +/- 0.03. Isolated islets were then cultured in vitro or transplanted into mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…46 Several analytical methods are available for the detection of insulin, including bioassays, [47][48][49] radioimmunoassays, 50 chemiluminescence immunoassays 51 and immunoenzymometric assays. 52 The most commonly used methods for the detection of insulin are mass spectrometry, 53 photolytic electrochemical detection 54 and high-performance liquid chromatography coupled with UV absorption 55 and fluorescence. 56 These methods are all time consuming; therefore, we wished to employ our OTFTs to detect the charge of insulin.…”
Section: Resultsmentioning
confidence: 99%
“…46 Several analytical methods are available for the detection of insulin, including bioassays, [47][48][49] radioimmunoassays, 50 chemiluminescence immunoassays 51 and immunoenzymometric assays. 52 The most commonly used methods for the detection of insulin are mass spectrometry, 53 photolytic electrochemical detection 54 and high-performance liquid chromatography coupled with UV absorption 55 and fluorescence. 56 These methods are all time consuming; therefore, we wished to employ our OTFTs to detect the charge of insulin.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of insulin is of great important for clinical diagnostics, because it is bound up with diabetes and has great applications in clinical pharmacology [21]. Bioassay, immunoassay and chromatographic methods [22] are three main procedures for determination of insulin. Although immunoassay of insulin has been widely used for determination of insulin in biological specimens, non-specific binding with the coexistent biomolecules against antiinsulin antibody and cross reaction are the major interferences with the precise determination of insulin in biosamples [23].…”
Section: Introductionmentioning
confidence: 99%
“…A similar value (118 ng/islet) was observed by HPLC with UV detection utilizing 20 islets. 7 Insulin content in mice (245 ( 59 ng/islet) was observed for the first time, although only the ratio of insulin types I to II obtained from mice was reported by Linde et al with the use of more than 1400 islets. 25 The calculated ratio of types I to II obtained from rats and mice were 1.4 ( 0.2 and 0.57 ( 0.01, respectively, which were consistent with the previous data reported by Linde et al 25 Kakita et al reported that insulin type I is predominant in mice, 26 whereas the result in the present experiment and the data reported by Linde et al 25 showed the predominance of type II.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to immunoassays, the chromatographic method is more reliable for selectivity because of the separation step included. High-performance liquid chromatography (HPLC) with UV detection 7 and, more recently, mass spectrometry (MS) with isotope dilution assay (IDA) 8 have been used for the determination of insulin. HPLC with UV detection, however, has poor sensitivity to detect insulin in biological samples; a picomole-level injection on column should be achievable.…”
Section: Rodents (Rat and Mouse) Have Two Types Of Insulin (Insulin I...mentioning
confidence: 99%